Survival of Escherichia coli after high-antibiotic stress is dependent on both the pregrown physiological state and incubation conditions - Thorfinnsdottir, Lilja Brekke; Bø, Gaute Hovde; Booth, James Alexander; Bruheim, Per (Frontiers in Microbiology, 2023)
The survival of bacterial cells exposed to antibiotics depends on the mode of action, the antibiotics concentration, and the duration of treatment. However, it also depends on the physiological state of the cells and the environmental conditions. In addition, bacterial cultures contain sub-populations that can survive high antibiotic concentrations, so-called persisters. Research on persisters is challenging due to multiple mechanisms for their formation and low fractions, down to and below one millionth of the total cell population. Here, we present an improved version of the persister assay, where the high-antibiotic stress is performed in different media. Survival of Escherichia coli strongly depended on whether the media supported growth. Much higher surviving fractions were observed in nutrient-limited conditions, but the results were also highly dependent on the type of antibiotic. Therefore, applying the same conditions is critical for consistent and comparable results. The physiological state of E. coli before antibiotic treatment was determined by quantitative mass spectrometry-based metabolite profiling. No direct connection was observed between antibiotic efficacy to the metabolic state. This also includes the energetic state (i.e., the intracellular concentration of ATP and the adenylate energy charge), which has earlier been hypothesized to be decisive for persister formation. The study provides guides and suggestions for the design of future experimentation in the research fields of persisters and antibiotic tolerance.